CONTRIBUIÇÃO DO DESIGN ESTRATÉGICO PARA A MOBILIDADE URBANA DE SÃO LUÍS: análise estratégica dos terminais de integração. - SILVA, Marcus Gusmão Ferreira Santos (2017)
The objective of this research was to relate the concepts of strategic design to urban mobility in São Luís. The MSDS - System Design Method for Sustainability - and the PSS - Product Product Service - analysis were used in the current public transportation scenario Of the city. Through this evaluation, we intend to discuss how strategic design can promote innovation in urban public services and propose future scenarios that generate sustainable urban mobility. As a result, it is concluded that the integration terminals are very relevant for public transport in São Luís, but these are underutilized, new forms of integration between other means of transport and new services could be implemented in addition to the Simple bus line change. In this way, at the end of the research, future scenarios were suggested to shape the present, generating an improvement in urban mobility in the city.